The current state and problems of formation of digital competence of teachers (Journal of Educational Sciences, 2023)
The digitalization process, which is currently rapidly developing at the global level, requiresqualified personnel with digital competencies. During the COVID-19 pandemic, the role of digitaltechnologies and its enormous didactic capabilities in the education system were reliably confirmedby the accumulation of experience in organizing distance learning and ensuring the continuity of theeducational process. The purpose of the study is to clarify the concept of digital competence and toidentify the level of its formation, problems of teachers in everyday practice. The article analyzes theresearch works of scientists from near and far abroad on the topic of the study, and the conclusions areformulated. The definition of the concept of “digital competence” is clarified and the components ofdigital competencies (emotional-volitional, social media-communicative, cognitive, activity, reflexiveevaluative)are highlighted and characterized in a meaningful way. The practical part of the studyinvolved 122 teachers of Karaganda, West Kazakhstan, Akmola, Atyrau and Kyzylorda regions whounderwent advanced training in IPK in 2019-2021. 14.6% of the teachers in the sample showed a low level of psychological readiness to work with digital technologies, the average level was 45.2%, and thehigh level was 41.2%. Adapted situational tasks on didactics and digitalization of education for teacherswere used to determine the level.Key words: global digitalization, digitalization of education, digital technology, teachers, digitalcompetence.